Serum from differently exercised subjects induces myogenic differentiation in LHCN-M2 human myoblasts. Issue 14 (18th July 2018) - Vitucci, D.; Imperlini, E.; Arcone, R.; Alfieri, A.; Canciello, A.; Russomando, L.; Martone, D.; Cola, A.; Labruna, G.; Orrù, S.; Tafuri, D.; Mancini, A.; et al.
ABSTRACT: Myogenesis is the formation of muscle tissue from muscle precursor cells. Physical exercise induces satellite cell activation in muscle. Currently, C2C12 murine myoblast cells are used to study myogenic differentiation. Herein, we evaluated whether human LHCN-M2 myoblasts can differentiate into mature myotubes and express early (myotube formation, creatine kinase activity and myogenin) and late (MyHC-β) muscle-specific markers when cultured in differentiation medium (DM) for 2, 4 and 7 days. We demonstrate that treatment of LHCN-M2 cells with DM supplemented with 0.5% serum from long-term (3 years) differently exercised subjects for 4 days induced myotube formation and significantly increased the early (creatine kinase activity and myogenin) and late (MyHC-β expression) differentiation markers versus cells treated with serum from untrained subjects. Interestingly, serum from aerobic exercised subjects (swimming) had a greater positive effect on late-differentiation marker (MyHC-β) expression than serum from anaerobic (body building) or from mixed exercised (soccer and volleyball) subjects. Moreover, p62and anti-apoptotic Bcl-2 protein expression was lower in LHCN-M2 cells cultured with human sera from differently exercised subjectst han in cells cultured with DM. In conclusion, LHCN-M2 human myoblasts represent a species-specific system with which to study human myogenic differentiation induced by serum from differently exercised subjects.